The Archetype of the “Grumpy Old Man”: Individuation and Wholeness in Fredrick Backman’s A Man Called Ove - Shabrina Almaira; Zuhrul Anam (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study examines the psychological transformation of the main character in Fredrik Backman’s novel A Man Called Ove through the lens of Carl Jung’s individuation theory. The research aims to explain how the individuation process enables an individual to overcome chronic loneliness and depression following the loss of a loved one. Using a qualitative descriptive method, the study analyzes narrative data, dialogues, and monologues categorized into Jungian archetypes: Persona, Shadow, Anima, and Self. The results demonstrate that Ove’s journey toward psychological wholeness begins with the failure of his defensive personas to resolve his inner suffering. This failure exposes his shadow, manifested through deep despair and repeated suicidal impulses. The findings further reveal the emergence of the anima, triggered by social interactions. This process culminates in the realization of the Self, where Ove achieves a supraordinate totality of the psyche, transitioning from isolation to communal belonging and social altruism. The study concludes that the individuation process allows for the transcendence of grief, leading to a state of psychological peace and a meaningful final legacy.